2011
DOI: 10.1103/physreva.83.023417
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-dependent interference effect in high-order harmonic generation from alignedH2+molecules

Abstract: Based on the nonperturbative quantum scattering theory of high-order harmonic generation (HHG) and using the linear combination of atomic orbitals theory of molecular orbitals, we derive the HHG rate formula for molecules. Employing the formula, we study the intensity dependence of the interference effect induced by the molecular structure. We find that the molecular HHG was modulated by the interference not only in the recombination process but also in the ionization process. The location of the interference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For the HHG of small linear molecules, there is a minimum in the harmonic spectra due to the interference of many atomic centers. [22][23][24][25][26][27] This minimum in the molecular HHG spectrum was first predicted theoretically by Lein et al [16,17] and confirmed experimentally by Kanai et al [23] The interference structure changes with the internuclear distance, the symmetry of molecular orbit, and the multi-orbit effect. [27,28] Thus, it is necessary to figure out the physical mechanism behind the interference structure in the molecular HHG spectrum.…”
Section: Introductionmentioning
confidence: 67%
“…For the HHG of small linear molecules, there is a minimum in the harmonic spectra due to the interference of many atomic centers. [22][23][24][25][26][27] This minimum in the molecular HHG spectrum was first predicted theoretically by Lein et al [16,17] and confirmed experimentally by Kanai et al [23] The interference structure changes with the internuclear distance, the symmetry of molecular orbit, and the multi-orbit effect. [27,28] Thus, it is necessary to figure out the physical mechanism behind the interference structure in the molecular HHG spectrum.…”
Section: Introductionmentioning
confidence: 67%
“…On the other hand, the HHG spectra from symmetric molecules show a striking minimum, [39] which has been identified as arising from the effect of two-center interference and has attracted broad interest in recent years. [40][41][42][43][44] It has been shown that this minimum in the HHG spectrum corresponds to the minimum in the bound-continuum transition dipole and therefore has important applications in molecular high-order harmonic spectroscopy (HHS). For example, this minimum in the HHG spectrum can be used to read the bond length of the molecule [40,41] and judge the phase of the dipole which is important in the molecular orbital tomography procedure.…”
Section: Introductionmentioning
confidence: 99%